Sabotage versus Discouragement: Which Dominates Post Promotion Tournament Behavior?. (14th January 2016) - Johnson, David; Salmon, Timothy C.
Abstract : We explore the behavior of losers of promotion tournaments after the tournament is concluded. We do so with an experiment in which we vary the design of the promotion tournament to determine how tournament design affects post tournament effort. Our design allows us to discriminate between two possible reasons tournaments might lead to decreased work effort among the tournament losers: strategic sabotage and a worker becoming discouraged by the tournament outcome. We examine behavior after the tournament and find evidence suggesting that bad tournament design can lead to workers being discouraged. This discouragement effect is strong for low ability workers but not for high ability workers. Conversely, we do find evidence that some high ability workers engage in strategic sabotage but the incidence does not vary with the design of the promotion tournament and the incidence of it is low.